(untitled) (Italian Journal of Public Health, 2005)
Background. Listeria monocytogenes is one of the most important human foodborne pathogens; it may be responsible for several disorders, like meningoencephalitis. Listerial isolation in cerebrospinal fluid (CSF) is often difficult using microbiologic traditional assays. The aim of this study is to evaluate the reliability of molecular techniques as an alternative tool in order to identify Listeria monocytogenes meningitis and in particular, to evaluate a real-time PCR and a conventional PCR for the target hlyA gene. Methods. In 2000-2004, 145 patients, without T-cell immunodeficiency, affected by meningoencephalitis of unknown origin were admitted to the Infectious Diseases Institute of Sassari, Italy; a lumbar puncture was performed at the time of hospital admission. Two different PCR techniques, i.e. RT-PCR and a conventional PCR, were performed in order to detect CNS listerial infection, in conjunction with traditional microbiologic assays. Results. We identified fourteen patients affected by listerial meningitis using RT-PCR and conventional PCR. All but one of the CSF cultures were negative for L. monocytogenes. Molecular techniques were performed on the CSF samples collected during follow-up revealing that signal intensity decreased by 40%, 80% and 100% at day 15, 30 and 55 respectively, from the start of antibiotic treatment. Conclusions. Considering the seriousness of CNS involvement caused by L. monocytogenes infection, prompt diagnosis is necessary in order to rapidly start specific treatment. Conventional PCR and RT-PCR are rapid assays for L. monocytogenes diagnosis and they might be useful for monitoring the efficacy of antibiotic therapy.